2021
DOI: 10.1071/es20010
|View full text |Cite
|
Sign up to set email alerts
|

The Antarctic ozone hole during 2018 and 2019

Abstract: While the Montreal Protocol is reducing stratospheric ozone loss, recent increases in some ozone depleting substance (ODS) emissions have been identified that may impact southern hemisphere climate systems. In this study, we discuss characteristics of the 2018 and 2019 Antarctic ozone holes using surface in situ, satellite and reanalysis data to gain a better understanding of recent ozone variability. These ozone holes had strongly contrasting characteristics. In 2018, the Antarctic stratospheric vortex was re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 74 publications
2
13
0
Order By: Relevance
“…While the 2020 ozone hole was smaller than that in 2015, when ozone depletion was influenced by volcanic aerosols and the general absence of dynamical variability in the polar vortex (Stone et al 2017;Tully et al 2019), it showed similar persistence. The evolution of the daily area metric in 2020 up to the end of October closely matched the behaviour in 2018, when the relative absence of strong dynamical activity was also a feature (Klekociuk et al 2021).…”
Section: Ozone Hole Metricssupporting
confidence: 60%
See 4 more Smart Citations
“…While the 2020 ozone hole was smaller than that in 2015, when ozone depletion was influenced by volcanic aerosols and the general absence of dynamical variability in the polar vortex (Stone et al 2017;Tully et al 2019), it showed similar persistence. The evolution of the daily area metric in 2020 up to the end of October closely matched the behaviour in 2018, when the relative absence of strong dynamical activity was also a feature (Klekociuk et al 2021).…”
Section: Ozone Hole Metricssupporting
confidence: 60%
“…We then synthesise the analysis to address our two key questions. This work complements analyses of earlier ozone holes presented in the following series of papers where further details on individual years discussed here can be obtained: , Tully et al (2011), Klekociuk et al (2014), Krummel et al (2019), Tully et al (2019) and Klekociuk et al (2021).…”
Section: Introductionsupporting
confidence: 58%
See 3 more Smart Citations